Teachers' Perception of the Gender Gap in STEAM Subjects in Pre-University Stages - María Sánchez-Jiménez; Pablo Fernández-Arias; Diego Vergara; Álvaro Antón-Sancho; José A. Orosa (MDPI AG, 2024)
The term STEAM (Science, Technology, Engineering, Arts and Mathematics) is associated with a promising pedagogical approach to improve the development of students at different educational stages. Degrees linked to a STEAM approach encourage real-world problem solving through the application of multidisciplinary knowledge. The objective of this research is to analyze the perception of Early Childhood and Primary to Secondary Education teachers on the existence of the gender gap among pre-university students in subjects related to STEAM degrees in Spain. Given the results obtained, it is possible to affirm that according to teachers, there is a gender gap among students in the early educational stages in topics related to STEAM careers, which can mark their future gender gap in university education. Given this scenario, it is necessary to continue researching the possible factors that influence the gender gap in these degrees to understand possible gender inequalities in the educational field. Furthermore, the need to implement educational strategies that promote gender equality in Spain from the first educational stages is highlighted.